7Li evolution in the thin and thick discs of the Milky Way. Issue 4 (27th November 2018) - Cescutti, G; Molaro, P
ABSTRACT: Recent detection of the isotope 7 Be (which decays into 7 Li) in the outbursts of classical novae confirms the suggestion made in the 1970s that novae could make 7 Li. We reconsidered the role of novae as producers of 7 Li by means of a detailed model of the chemical evolution of the Milky Way. We showed that novae could be the Galactic 7 Li source accounting for the observed increase of Li abundances in the thin disc with stellar metallicity. The best agreement with the upper envelope of the observed Li abundances is obtained for a delay time of ≈1 Gyr for nova production and an effective 7 Li yield of 1.8(± 0.6)×10 −5 M⊙ over the whole nova lifetime. Lithium in halo stars is depleted by ≈0.35 dex, assuming the pristine abundance from standard big-bang nucleosynthesis. We elaborate a model that matches the pristine stellar abundances, assuming that all stars are depleted by 0.35 dex. In this case, the delay remains the same, but the Li yields are doubled compared with the previous case. This model also has the merit of matching the Li abundance in meteorites and young T Tauri stars. A thick disc model, adopting the parameters derived for the thin disc, can also explain the absence of an increase of Li abundance in its stars. The thick disc is old, but formed and evolved in a time shorter than that required by novae to contribute significantly to 7 Li. Therefore, no 7 Li enhancement is expected in thick disc stars. We show that the almost constant Li abundance in the thick disc results from the compensation of stellar astration by spallation processes.